1976
DOI: 10.3109/07435807609052927
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Thyroid Hormones and Erythrocyte Membranes: Competitive Inhibition of Binding131I-L-Triiodothyronine and131I-L-Thyroxine by Their Analogs

Abstract: Molecular structural characteristics of thyroid hormones which influence binding to the erythrocyte membranes were investigated by competitive binding experiments. The ability of thyroid hormone analogs to displace 131 I-L-thyroxine and 131 I-L-triiodothyronine from the membranes was considered evidence of their competitive binding. The diphenyl ether linkage (thyronine) was essential as compounds with a single aromatic ring were weakly competitive. The presence of three iodine atoms at 3, 5 and 3' positions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…It is clear that the RBC membrane binds T 4 and T 3 with comparable affinity (Fig. 1B), as shown by others (Crispell, Coleman and Hyer 1957;Singh, Carter, Kydd and Costanzo 1976), but that well-recognized differences in plasma binding protein affinities for T 4 and T 3 (Oppenheimer 1968) condition a frank difference in erythrocyte uptake of these two hormones in the presence of such proteins (Fig. 1A).…”
Section: Discussionsupporting
confidence: 74%
“…It is clear that the RBC membrane binds T 4 and T 3 with comparable affinity (Fig. 1B), as shown by others (Crispell, Coleman and Hyer 1957;Singh, Carter, Kydd and Costanzo 1976), but that well-recognized differences in plasma binding protein affinities for T 4 and T 3 (Oppenheimer 1968) condition a frank difference in erythrocyte uptake of these two hormones in the presence of such proteins (Fig. 1A).…”
Section: Discussionsupporting
confidence: 74%
“…From these data, it is also clear that the iodine at position 5' is not necessary for thyroid hormone binding to these mem branes. This latter finding contrasts with the importance of the degree of iodination of thy roid hormone analogues for optimal binding to the serum transport proteins, such as thy roxine-binding globulin and thyroxine-bind ing prealbumin, or nuclear receptor [2,32], In agreement with the present data, however, studies using erythrocyte plasma membranes have shown that the iodine at position 5' is not critical for thyroid hormone analogues binding to rabbit erythrocyte membranes [33] and in the activation of Ca2+ ATPase in hu man red cell membrane ghosts [34], The data reported herein demonstrate a generally good correlation between the relative affinity of thyroid hormone analogues for brush border membranes and their relative in vivo biologi cal activity except that the luminal binding sites show equal affinity for T 3 and the less biologically active T4. However, the conver sion of T4 to T 3 is an important function of the liver and kidneys in contributing to the level of intracellular T 3 in various target tis sues that are incapable of converting T 4 to T 3 [11,35,36], Accordingly, this result may not be surprising if it is assumed that these apical binding sites have a functional role in the recovery by renal cells of T4 filtered at the glo merulus, allowing its intracellular deiodination.…”
Section: Discussioncontrasting
confidence: 56%
“…Specific binding sites for thyroid hormones have been reported on target cell plasma membranes (Pliam & Goldfine 1977;Singh et al 1976;Tata 1975). It is also possible therefore that the uptake of thyroid hormones, especially L-triiodothyro¬ nine, could be mediated in part by a plasma mem¬ brane transport system (Christensen et al 1954;Stitzer & Jacquez 1975).…”
Section: Discussionmentioning
confidence: 96%